Considerations for future studies on the effect of late phase oxygen strategies on retinopathy of prematurity - Nusman, Charlotte M.; Schalij-Delfos, Nicoline E.; Groenwold, Rolf H. H.; Onland, Wes (Frontiers in Pediatrics, 2022)
Strategies to ensure high intraocular oxygen delivery to the developing retina after 32 weeks gestational age, such as higher saturation targets and/or higher hemoglobin levels, are hypothesized to prevent ophthalmological treatment for retinopathy of prematurity (ROP). This short report summarizes the current evidence of these strategies, and discusses possibilities of future studies. A large sample size would be required and therefore the feasibility of a future randomized controlled trial is questioned.